2018
DOI: 10.1186/s13071-018-2905-6
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of long non-coding RNA expression profiles in monocytic myeloid-derived suppressor cells in Echinococcus granulosus-infected mice

Abstract: BackgroundCystic echinococcosis is a worldwide chronic zoonotic disease caused by infection with the larval stage of Echinococcus granulosus. Previously, we found significant accumulation of myeloid-derived suppressor cells (MDSCs) in E. granulosus infection mouse models and that they play a key role in immunosuppressing T lymphocytes. Here, we compared the long non-coding RNA (lncRNA) and mRNA expression patterns between the splenic monocytic MDSCs (M-MDSCs) of E. granulosus protoscoleces-infected mice and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…HIV, porcine circovirus 2, HSV-1, rabies virus, avian leukosis virus J, bovine viral diarrhea virus) and parasites (e.g. Echinococcus granulosus, Cryptosporidium parvum, Cryptosporidium baileyi) in animals and humans [28,33,[66][67][68][69][70][71][72][73]. The expression profiles of host circRNAs were also elucidated after infections of avian leukosis virus J [74], bovine viral diarrhea virus [75], human cytomegalovirus [76], Orf virus [30], porcine endemic diarrhea virus [29], HIV [77], transmissible gastroenteritis virus [78], Mycobacterium tuberculosis [79], Clostridium perfringens [80] and C. baileyi [33].…”
Section: Discussionmentioning
confidence: 99%
“…HIV, porcine circovirus 2, HSV-1, rabies virus, avian leukosis virus J, bovine viral diarrhea virus) and parasites (e.g. Echinococcus granulosus, Cryptosporidium parvum, Cryptosporidium baileyi) in animals and humans [28,33,[66][67][68][69][70][71][72][73]. The expression profiles of host circRNAs were also elucidated after infections of avian leukosis virus J [74], bovine viral diarrhea virus [75], human cytomegalovirus [76], Orf virus [30], porcine endemic diarrhea virus [29], HIV [77], transmissible gastroenteritis virus [78], Mycobacterium tuberculosis [79], Clostridium perfringens [80] and C. baileyi [33].…”
Section: Discussionmentioning
confidence: 99%
“…The conservation of miRNAs that are involved in Echinococcus regulation reflects the complex and sophisticated adaptations, which are necessary for different environments, present within the life cycles of parasitic species. High-throughput sequencing and miRNA microarray analyses identified dysregulated miRNAs present during parasite infection in natural hosts and animal models that were present in relevant cells, tissues, and blood; demonstrating the importance of these miRNAs in host responses to pathogen challenges [19,43,55]. Recent research results have shown that circulating non-coding RNAs, including miRNAs and lncRNAs, can be stably detected in the blood of hosts that were infected with E. granulosus and E. multilocularis [19,43,56] (Table 3).…”
Section: Common Mirnas In Echinococcus Sppmentioning
confidence: 99%
“…Large miRNAs, being identified in E. granulosus, E. multilocularis, and E. canadensis (G7), have been found to feature certain characteristics of genes in expression regulation, such as tissue and developmental stage specificity, in their respective hosts [18,19,43]. To date, the miRNA expression profiles of E. granulosus sensu stricto (76 known miRNAs, including adults, cysts, and protoscoleces) [44,45], E. canadensis (46 known miRNAs, including cysts and protoscoleces) [12,46], and E. multilocularis (46 known miRNAs, including cysts) [1] have been reported (Table 1).…”
Section: Widespread Expression Of Mirnas In Echinococcus Spp Accordimentioning
confidence: 99%
See 2 more Smart Citations